The Effect of Intellectual Capital and Sustainability Reporting Disclosure on Financial Performance with Corporate Governance Mechanism as Moderating Variable (Empirical Study on Companies Listed on the Indonesia Stock Exchange in 2017–2021) - Marilis, Marsheila Aprilia Pimpy; Subiyanto, Bambang; Meini, Zumratul (KnE Social Sciences, 2024)
This study aims to analyze the effect of Intellectual Capital and Sustainability Reporting Disclosure on the Financial Performance with Corporate Governance Mechanisms as Moderating Variables on companies listed on the Indonesia Stock Exchange for the 2017–2021 period. This study uses 125 sample firms selected through a purposive sampling method. Data were analyzed using the Partial Least Square (PLS) model. The results of this study indicate that Intellectual Capital has no significant effect on Financial Performance and Sustainability Reporting Disclosure has a significant positive effect on Financial Performance. Corporate Governance Mechanisms can moderate the influence of Intellectual Capital and Disclosure of Sustainability Reporting on Financial Performance. The results of this study have implications for companies to pay more attention to investment through intellectual capital and sustainability reporting, and maintain good corporate governance as a form of internal supervision, because it can affect company performance. Keywords: intellectual capital, sustainability reporting disclosure, corporate governance mechanism and financial performance